2008
DOI: 10.1158/1541-7786.mcr-07-0355
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate Inhibits Proliferation and Exerts an Antifibrotic Effect in Human Breast Stroma Fibroblasts

Abstract: Tumor stroma plays an important role in cancer development. In a variety of tumors, such as breast carcinomas, a desmoplastic response, characterized by stromal fibroblast and collagen accumulation, is observed having synergistic effects on tumor progression. However, the effect of known anticancer drugs on stromal cells has not been thoroughly investigated. Imatinib mesylate is a selective inhibitor of several protein tyrosine kinases, including the receptor of platelet-derived growth factor, an important med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…Moreover, a recent report suggests that PRL may act directly on tumor-associated fibroblasts (76) in addition to enhancing collagen realignment in stiff matrices as reported herein. Tyrosine kinase inhibitors, which block activation of ERK1/2 and AKT, inhibit both proliferation and collagen synthesis in tumor-associated fibroblasts (77). In light of the ability of PRL to potently cooperate with growth factors to activate these signaling pathways (15,16), these interactions deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent report suggests that PRL may act directly on tumor-associated fibroblasts (76) in addition to enhancing collagen realignment in stiff matrices as reported herein. Tyrosine kinase inhibitors, which block activation of ERK1/2 and AKT, inhibit both proliferation and collagen synthesis in tumor-associated fibroblasts (77). In light of the ability of PRL to potently cooperate with growth factors to activate these signaling pathways (15,16), these interactions deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicate that Imatinib treatment decreased the concentration of some soluble growth stimulants secreted by CAFs in the conditioned media, resulting in a decrease of proliferative activity of lung cancer cells. We suspect that the decrease was mainly due to the reduced number of CAFs because of blocking PDGF signaling by Imatinib, based on the findings that Imatinib inhibited DNA synthesis in CAFs (28) and increased the incidence of apoptosis in CAFs (29). However, we have not yet been able to identify the soluble growth stimulants secreted by CAFs and involved in the increase of proliferation of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are a major component of tumor stroma in many solid tumors. It is suggested therefore that inhibition of fibroblast activity could lead to suppression of tumor development and progression (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been carried out to target stromal fibroblasts using tyrosine kinase inhibitor, such as dasatinib or imatinib (Mueller et al, 2007a;Gioni et al, 2008;Haubeiss et al, 2010). Mueller et al (2007a) showed that imatinib inhibits proliferation and modulates cytokine expression of human cancerassociated fibroblasts from colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%